An efficient algorithm to improve oil-gas pipelines path - Naeem Hasan Almaalei, Nabeel; Noor Asyikin Mohd Razali, Siti; Abdulwahab Mohammed Alduais, Nayef (International Journal of Engineering and Technology, 2019)
Oil-gas pipeline is a complex and high-cost system in terms of materials, construction, maintenance, control, and monitoring in which it involves environmental, economic and social risk. In the case study of Iraq, this system of pipelines is above the ground and is liable to accidents that may cause environmental disaster, loss of life and money. Therefore, the aim of this study is to propose a new algorithm to obtain the shortest path connecting oil-gas wells and addressing obstacles that may appear on the path connecting any two wells. In order to show the efficiency of the proposed algorithm, comparison between ant colony optimization (ACO) algorithm and a real current method of linking is used for this purpose. Result shows that the new proposed algorithm outperformed the other methods with higher reduction in operational cost by 16.4% for a number of 50 wells. In addition, the shortest path of connecting oil-gas wells are able to overcome all the addressed obstacles in the Rumaila north field, which is located in the city of Basra in southern Iraq.